PENGEMBANGAN MODEL PENILAIAN KUALITAS TERJEMAHAN - Mangatur Nababan; Ardiani Nuraeni; Sumardiono . (Kajian Linguistik dan Sastra, 2012)
The main objective of this study is to produce a model of TQA from English into Indonesian. It employed a descriptive-qualitative approach. Its data were obtained through content analysis, interviewing with key informants, FGD and observation, and analyzed with an interactive data analysis technique. The final findings of this research indicate the followings. First, the Model of TQA produced assesses the quality of translation holistically. Second, the Model is applicable for assessing the quality of translation within the contexts of translation research and teaching and of professional settings. Third, the Model opens opportunities for raters to assess various units of translation, ranging from micro to macro levels. Fourth, the effectiveness of the Model in assessing quality of translation depends solely on the ability of the assessors or raters in applying it in various settings. Prior to its application, those engaged in every translation quality assessment should read and understand all relevant information and procedures of how it should be employed.